The Application of The Maritime Ethnoscience Approach in Science Education: A Systematic Literature Review - Junus, Nur Azizah Dj.; Sriastuti, Nyoman; Panyo, Risna Harun; Hasim, Hasim; Sidik, Abubakar (STKIP HARAPAN BIMA, 2025)
This study aims to examine the application of a maritime ethnoscience approach in science learning through a systematic literature review (SLR) of publications from 2017 to 2025. Of the 60 articles searched through Google Scholar and Scopus, 21 passed the selection process based on the inclusion criteria. The analysis shows that most studies focused on junior high school students, utilizing direct ethnoscience learning models, 4D development, and Problem-Based Learning (PBL). This review confirms that the application of maritime ethnoscience is effective in improving students' conceptual understanding, scientific literacy, critical thinking skills, and awareness of the marine environment. However, the limited concentration of research on a single educational level suggests opportunities for further study at the elementary, high school, and tertiary levels. These findings emphasize the urgency of integrating maritime local wisdom into science learning, not only to strengthen cultural identity but also to equip students with 21st-century competencies.